Multi-Element Composition and 87Sr/86Sr of Wines and Their Potentialities as Fingerprints of Wine Provenance - Marisa,C. (2003)
The potentialities of both multi-element composition and the ratio 87Sr/86Sr as tracers of wine provenance were evaluated, by studying the relative influence of the provenance soil and vinification process on these two parameters. With this purpose, two wines were selected: one red table wine and one red fortified wine, both from the Douro wine-district, Portugal. The values of the 87Sr/86Sr ratio were also determined in ten wines of different regions of origin. Both vinification processes changed the multi-element composition of the wines. Nevertheless, significant and linear correlations were obtained between the patterns of the wines and that of the respective musts prepared in the laboratory (without contact with the vinification system), as well as between those of the wine and of the provenance soil. Regarding 87Sr/86Sr, statistically identical values were found in the wines, respective musts and provenance soil. In addition, significant differences in the 87Sr/86Sr ratios were found in wines from different regions of origin. Therefore, the multi-element composition together with the 87Sr/86Sr ratio showed to be suitable to act as fingerprints of the origin of a wine. A database of these parameters in different wines will be very useful for discriminating wines by regions in order to detect/prevent wine fraud.